Reshoring by Decree? The Effects of Decoupling Europe from Global Value Chains - Alexander Sandkamp (Intereconomics, 2022)
Overall, decoupling from certain countries may be both politically necessary and economically feasible, at least in the long run. However, a general shift of production back to Europe would be accompanied by significant losses in real income.
Keywords: F11; F13; F17; 330